BEACH DEBRIS ON LABUANGE BEACH, BARRU DISTRICT, SOUTH SULAWESI PROVINCE, INDONESIA - Isyrini, Rantih; Tambaru, Rahmadi; La Nafie, Yayu A.; Ukkas, Marzuki; Cordova, Muhammad Reza (Hasanuddin University, 2018)
To support the efforts of the Indonesian government in managing marine debris that has a broad potential negative impact in various aspects, beach debris monitoring activities are urgently required in various locations. This research was carried out from June to August 2018 in the west coast region, on Labuange beach, Barru Regency, South Sulawesi Province, Indonesia, which was exposed by the Indonesian Through-Flow. The study aimed to determine the amount, weight and composition of marine debris on Labuange beach. Marine debris was sampled from a permanent line transect with an area of 150 m2 (three replications). Samples were then cleaned, sorted, counted, and weighed. The average amount of marine debris was 5.98 + 2.13 items/m2 per month, with a total weight was 138.69 ± 91.32 g/m2 per month. Plastic and rubber category dominated every sampling period in the location. The abundance of marine debris, both regarding quantity and weight, fluctuated in high amount during the sampling period, which indicated the magnitude of the role of oceanographic factors, including the direction of waves, and lack of community awareness on marine debris impacts and management. The great amount and weight of marine debris and the type of waste, which was dominated by plastic and rubber is a potential threat to humans, marine biota, and the local or global environment.